Guiding Quality Diversity on Monotone Submodular Functions: Customising the Feature Space by Adding Boolean Conjunctions - Schmidbauer, Marcus; Opris, Andre; Bossek, Jakob; Neumann, Frank; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2024, Melbourne, VIC, Australia, July 14-18, 2024)

On the Effectiveness of Heterogeneous Ensemble Methods for Re-Identification - Klüttermann, Simon; Rutinowski, Jérôme; Polachowski, Frederik; Nguyen, Anh; Grimme, Britta; Roidl, Moritz; Müller, Emmanuel (International Conference on Machine Learning and Applications, ICMLA 2024, Miami, FL, USA, December 18-20, 2024)

Generalised Kruskal Mutation for the Multi-Objective Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2024, Melbourne, VIC, Australia, July 14-18, 2024)

Benchmarking Sentence Embeddings in Textual Stream Clustering with Applications to Campaign Detection - Stampe, Lucas; Stockdiek, Janina Lütke; Grimme, Britta; Grimme, Christian (International Joint Conference on Neural Networks, IJCNN 2024, Yokohama, Japan, June 30 - July 5, 2024)

Wissensmanagement in Feuerwehren skalierbare IT-Architektur für Erweiterung und Austausch - Schultz, Andreas Maximilian; Mozgova, Iryna

Rezension zu: „The Nordic Bible. Bible Reception in Contemporary Nordic Societies“ - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 147)

Weather-induced emergency situations: Extreme data in situational awareness and visualisation - Gräßler, Iris; Pottebaum, Jens; Hieb, Michael; Pratzler-Wanczura, Sylvia; Krüger, Oliver; Kruijff, Ivana; Rupp, Nicola (Proceedings of the Days of Security Research 2023)
Extreme weather situations increasingly lead to hazardous situations with high demands on de-cision-making and communication. Weather and impact forecasts serve to prepare for such an emergency situation, and extreme data must be processed during operations. Therefore, extreme data is categorised with reference to global weather data and data from local situation reconnais-sance using sensors carried by mobile robots. A concept is presented in which information quality is explicitly considered in visualization for situational awareness. This extends existing principles of information visualisation with regard to the uncertainty resulting from extreme data. The re-sults are intended to help decision-makers at different management levels to make informed decisions.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

N2O oxidized combustion of ethylene: Detailed laminar flame structure and the significance of oxidizer decomposition kinetics for modeling - Hoener, Martin; Bierkandt, Thomas; Shaqiri, Shkelqim; Kasper, Tina (Proceedings of the Combustion Institute)

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Vermittlungshorizonte. Erziehungswissenschaftliche Reflexionen über hochschul- und wissenschaftsdidaktische Herausforderungen - Freitag, Christine (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Which Media for Whom? The Implementation of Microgrids as a Trigger of Transformational Adult Learning Opportunities in Formal, Informal and Situational Settings in Times of Change - Asiimwe, Henry; Bode, Henrik; Bogere, Paul; Freitag, Christine; Mangeni, Teddy (Bildungsmedien für Erwachsene Educational Media for Adults)

Transformation durch Vermittlung. Das Heilige in der Geschichte pädagogischen und literarischen Wirkens der Jesuiten in Lateinamerika - Freitag, Christine; Thiem, Annegret ((Un)verfügbar - Kulturen des Heiligen)

Der Briefroman als Medium weiblicher Kritik in der Aufklärung – Einblicke in Caroline Rudolphis »Gemälde weiblicher Erziehung« - Vochatzer, Stefanie (»Debattieren, Opponieren, Protestieren – Interdisziplinäre Perspektiven auf sprachliche Praktiken des Widersprechens«)

Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures. SAND 2024: 15:1-15:20 - Scheideler, Christian; Hinnenthal , Kristian; Liedtke, David Jan

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter. - Scheideler, Christian; Padalkin, Andreas

Universal Coating by 3D Hybrid Programmable Matter. - Scheideler, Christian; Kostitsyna, Irina; Liedtke, David Jan

The structural power of reconfigurable circuits in the amoebot model. - Scheideler, Christian; Padalkin, Andreas; Warner, Daniel (The structural power of reconfigurable circuits in the amoebot model. Nat. Comput. 23(4): 603-625 (2024))

Routing schemes for hybrid communication networks. - Scheideler, Christian; Coy, Sam; Czumaj, Arthur; Schneider, Philipp; Werthmann, Julian (Routing schemes for hybrid communication networks. Theor. Comput. Sci. 985: 114352 (2024))

Invited Paper: Blockchains made Lightweight: A Median Rule for State Machine Replication. - Scheideler, Christian; Dou, Jinfeng